SOCIAL-EMOTIONAL COMPETENCE: EMPIRICAL EVIDENCE FROM INDONESIAN PRE-SERVICE TEACHERS OF ISLAMIC ELEMENTARY EDUCATION - Khunaivi, Herman; Kurniasih, Esti; Suryati, Nunung (UIN Sunan Kalijaga Yogyakarta, 2023)
Over the past two decades, research on the central role of teachers' social-emotional competencies (SEC) in their teaching abilities has increased rapidly. However, there is not much research that focuses on increasing the social-emotional competence of pre-service teachers. This study aims to explore the impact of pre-service teachers' SECon their English language teaching to young learners at the elementary level. Investigating how pre-service teachers develop their SEC at the elementary school level. This research used a qualitative method with seven prospective Islamic elementary school teachers as participants. Data collection in the research used observations and semi-structured interviews with prospective Islamic elementary school teachers who taught English to young students in fifth grade at the elementary level. Inductive data analysis was carried out in this research with stages of data reduction, data presentation, and drawing conclusions or verification. The research results show that pre-service teachers' social-emotional competencies are critical in avoiding burnout, improving well-being, and creating a positive learning environment. Pre-service teachers can begin to develop their social-emotional competencies by cultivating self-awareness. When pre-service teachers are aware of their emotions, they feel more in control of students in the classroom and make better decisions during the teaching and learning process.